Epidemiology of Uterine Cancer in Sarawak, Borneo, A 20-Year Review - Diana, Jawa; Kung, Yee Wong; Mastulu, Wahab; Azizah, Azhar; Emmanuel Joseph, Fong; Eunice Melissa, Joseph; Johnny, Pangkas; Choo, Huck Ooi (Asian Pacific Organization for Cancer Prevention (APOCP), 2024)
Objective: This study aimed to determine the epidemiology of uterine cancer in Sarawak, Malaysia, using data from a population-based cancer registry. Methods: The study population included all women diagnosed with uterine cancer in Sarawak, Malaysia between January 1996 and December 2015. Data on demographic and clinical characteristics were obtained from the Sarawak Cancer Registry. The crude incidence rate, age-standardized incidence rate (ASR), and incidence risk ratios (IRR) were calculated. Joinpoint regression analyses were performed to assess trends in incidence rates. Results: A total of 811 women were diagnosed with primary uterine cancer during the study period. The overall crude incidence rate for uterine cancer in Sarawak for the period 1996-2015 was 3.7 per 100,000. The ASR was 4.4 per 100,000 with a 95% CI (4.1-4.8). The ASR in 2011-2015 is 1.6 times higher than the ASR of uterine cancer in 1996- 2000. Higher incidence rates were observed in women aged 40-59 years and those aged 60 years and above. Chinese women had the highest ASR, followed by Malay and Iban women. Joinpoint regression analyses showed a significant increase in cases of uterine cancer among all ethnic groups and age groups. Conclusion: The incidence of primary uterine cancer in Sarawak, Malaysia, has increased over the past 20 years, with higher incidence rates observed in older age groups and among Chinese women. The findings suggest the need for continued efforts to improve the prevention, early detection, and treatment of uterine cancer in Sarawak